Child sexual abuse, adolescent/adult sexual violence, and sexual functioning among college women: a systematic review - Prachi H. Bhuptani; Elizabeth Mayer; Georgia Chan; Lindsay M. Orchowski (BMC, 2024)
Abstract Background Sexual violence, including childhood sexual abuse and adolescent/adult sexual assault, is a major public health concern, especially for college women. Sexual violence is associated with numerous negative consequences, including difficulties relating to sexual functioning. The current systematic review aimed to synthesize the existing research literature examining the association between sexual violence on sexual functioning among college women. Methods Only peer-reviewed articles reporting original data and written in English, which assessed for sexual functioning and sexual violence among a sample of college women, were included in the review. Articles were included if the research study assessed sexual violence occurring in childhood, adolescence, or adulthood. Results A total of 21 articles met these inclusion criteria and were included in the synthesis of the literature. In studies of college women, sexual violence occurring in adulthood was associated with worse sexual functioning outcomes among college women in 7 of the 21 studies. Findings were mixed regarding the association between childhood sexual abuse and sexual functioning among college women. Further, in three studies, psychological symptoms (e.g., depression, anxiety) mediated the association between sexual violence in adulthood and worse sexual functioning among college women. Studies varied in what domains of sexual functioning were assessed, and as a result, a limited number of studies included assessments of the same domain of sexual functioning. Further, some studies did not assess sexual violence at multiple points in development (i.e., childhood, adolescence, adulthood). Conclusions Future studies with longitudinal designs and a wider range of sexual functioning outcomes are needed, including studies focused on women attending 2-year and technical colleges.